2017
DOI: 10.1002/jbm.a.36163
|View full text |Cite
|
Sign up to set email alerts
|

Alkyl chitosan film‐high strength, functional biomaterials

Abstract: Biofilm with strong tensile strength is a topic item in the area of tissue engineering, medicine engineering, and so forth. Here we introduced an alkyl chitosan film with strong tensile strength and its possibility for an absorbable anticoagulation material in vivo was tested in the series of blood test, such as dynamic coagulation time, plasma recalcification time and hemolysis. Alkyl chitosan film was a better biomaterial than traditional chitosan film in the anticoagulation, tissue compatibility and cell co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…It is then clear that innovation in the field of loco-regional drug administration is a viable strategy to increase the effectiveness of chemotherapy and to reduce toxic side effects for lung cancer patients undergoing chemotherapy (38). In the case of the two materials studied in this research, chitosan, despite being a material used often for implants and for tissue engineering (39) and considered biocompatible and relatively non pro-inflammatory (40), showed a strong foreign body reaction and released cisplatin at an extremely low rate in vitro as well as in vivo. However, recently it has been reported that chitosan can show mild to moderate chronic inflammation (41) and foreign body reaction (42) in the case of crosslinked chitosan derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…It is then clear that innovation in the field of loco-regional drug administration is a viable strategy to increase the effectiveness of chemotherapy and to reduce toxic side effects for lung cancer patients undergoing chemotherapy (38). In the case of the two materials studied in this research, chitosan, despite being a material used often for implants and for tissue engineering (39) and considered biocompatible and relatively non pro-inflammatory (40), showed a strong foreign body reaction and released cisplatin at an extremely low rate in vitro as well as in vivo. However, recently it has been reported that chitosan can show mild to moderate chronic inflammation (41) and foreign body reaction (42) in the case of crosslinked chitosan derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…When amino and aldehyde react together, the reaction product is reduced with sodium cyanoborohydride (NaBH 3 CN) or sodium borohydride (NaBH 4 ) to obtain alkylated CS (AC) derivatives. The direct reaction between CS and halogenated alkyl groups under alkaline conditions can also produce AC derivatives (Figure 2A) [76,77]. Kurita et al [78] carried out the N-alkylation of CS with NaHCO 3 as an alkylating agent and accelerator in the aqueous phase and obtained N-carboxymethyl and N-phenyl CS with a high degree of substitution.…”
Section: Alkylation Reactionmentioning
confidence: 99%
“…[27][28][29] However, CS has poor mechanical strength which is not useful in certain applications. 27 We have incorporated graphene assembled porous carbon as the filler in polymer complex. Correspondence to: S. N. Kale; e-mail: sangeetakale2004@gmail.com nanofillers.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, chitosan (CS) is used, which is semicrystalline, biocompatible, 22 and biodegradable chitin derivative obtained from deacetylation of chitin under enzymatic or alkaline conditions [23][24][25] having applications in numerous biomedical community such as tissue regeneration, 26 agricultural, 27 and drug delivery. [27][28][29] However, CS has poor mechanical strength which is not useful in certain applications. This can be overcome by the incorporation of Additional Supporting Information may be found in the online version of this article.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation